Protocolos de sincronização da ovulação para inseminação artificial com tempo fixo em ovelhas - Almeida, Marcelo Ferreira de (2009)
The aim of study was to test the hormonal protocol for FTAI (fixed timed artificial insemination) with progesterone for 6 days applying eCG (Equine Corionic Gonadotrophin) or BE (Estradiol Benzoate) and induction of estrus using: MAP (acetato de medroxiprogesterone) for 6, 9 and 14 days or a single dose of PGF2a or male effect. Experiment 1: In D0 each ewe (n = 31) received CIDR being divided into 3 groups: GC (control) CIDR for 9 days and in withdrawal PGF2a + eCG. In G-eCG CIDR for 6 days PGF2a + eCG and in G-BE estradiol benzoate 24H after PGF2a and the FTAI 50H after the withdraw of CIDR. Experiment 2: On day 0 the sheeps (n = 48) received MAP being divided into 2 groups: G-9 and G-14 MAP by 9 or 14 days + PGF2a in withdrawal and detection of estrus. Experiment 3: divided up the sheeps (n = 151) in 3 groups: the G-6, each ewe received MAP for 6 days + PGF2a in withdrawal, the G-PGF, each ewe received PGF2a and G-EF only introducing ruffians. In exp. 1 pregnancy in the G-eCG (66%) was higher (p <0.05) in which G-BE (11.1%). In exp. 2 there were no differences (p <0.05) in estrus, pregnancy rate or design and in exp. 3 in G-6 (58%) and G-PGF (39%) the rate of estrus was greater (p <0.05) than in G-EF (11%). We concluded that is possible to reduce the time of permanence of progesterone using eCG for FTAI in sheep.